Prevalence of Lp(a) in a real-world Portuguese cohort: implications for cardiovascular risk assessment - Miguel Saraiva; Jonatas Garcez; Beatriz Tavares da Silva; Inês Poças Ferreira; José Carlos Oliveira; Isabel Palma (Lipids in Health and Disease)
Abstract Background Cardiovascular disease (CVD) is a major cause of mortality worldwide, necessitating more refined strategies for risk assessment. Recently, lipoprotein(a) [Lp(a)] has gained attention for its distinctive role in atherosclerosis, yet its prevalence and impact for cardiovascular risk assessment are not well-documented in the Portuguese population. This study aimed to characterize Lp(a) levels in a real-world Portuguese cohort, investigating its prevalence and association with CVD risk. Methods Retrospective and cross-sectional study of adults who underwent serum Lp(a) analysis in a Portuguese hospital between August 2018 and June 2022. Demographic and anthropometric data, laboratory values, relevant comorbidities and lipid-lowering medication were collected. Results Of 1134 participants, 28.7% had elevated Lp(a) levels (> 125 nmol/L). A higher prevalence was observed in those with atherosclerotic cardiovascular disease (ASCVD) (45.9%) or a family history of premature CVD (41.9%). Additionally, a significant association was found between elevated Lp(a) levels and traditional CVD risk factors, including hypertension, dyslipidemia, and diabetes mellitus. Among those classified as having low-to-moderate CVD risk by (Systematic COronary Risk Evaluation 2) SCORE2, 55.7% exhibited high Lp(a) levels (> 75 nmol/L), suggesting a potential higher risk of CVD disease. Conclusions The prevalence of elevated Lp(a) in Portugal, notably among those with ASCVD or premature CVD history, is concerning. This study underscores the potential of Lp(a) assessment for a more comprehensive approach to cardiovascular risk assessment. This could improve the stratification of CVD risk and identify individuals who could benefit from early intensive management of their risk factors, ultimately reducing the burden of CVD and cardiovascular-related mortality.